2021
DOI: 10.1186/s12938-021-00879-3
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelasticity measured by shear wave elastography in a rat model of nonalcoholic fatty liver disease: comparison with dynamic mechanical analysis

Abstract: Background Nonalcoholic fatty liver disease (NAFLD) is rapidly becoming one of the most common liver diseases. Ultrasound elastography has been used for the diagnosis of NAFLD. However, clinical research on steatosis by elastography technology has mainly focused on steatosis with fibrosis or non-alcoholic steatohepatitis (NASH), while steatosis without fibrosis has been poorly studied. Moreover, the relationship between liver viscoelasticity and steatosis grade is not clear. In this study, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…[ 39–41 ] However, the accumulation of lipids that characterizes NAFLD enhances the viscous behavior of the surrounding tissue. [ 41–43 ] This peculiar aspect is due to the viscosity of triglycerides being significantly higher than the one of water. [ 44 ] In light of these, s‐Hep3Gel effectively mimics the biomechanics of hepatic steatosis, as the values of G′ and G″ are coherent with those proposed by literature.…”
Section: Discussionmentioning
confidence: 99%
“…[ 39–41 ] However, the accumulation of lipids that characterizes NAFLD enhances the viscous behavior of the surrounding tissue. [ 41–43 ] This peculiar aspect is due to the viscosity of triglycerides being significantly higher than the one of water. [ 44 ] In light of these, s‐Hep3Gel effectively mimics the biomechanics of hepatic steatosis, as the values of G′ and G″ are coherent with those proposed by literature.…”
Section: Discussionmentioning
confidence: 99%
“…SWE can quantitatively reflect tissue stiffness according to shear wave propagation in the tissue expressed as Young's modulus. Zhaoke Pi et al [ 28 ] showed that the elasticity values µ attained by SWE in vivo had a significant correlation with liver steatosis in NAFLD in a mouse model. Grimal et al [ 29 ] found a steadily increase of median liver stiffness in rats with NASH, measured by SWE, with exacerbation of steatosis grade.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency response in the KVFD model undergoes a monotonically increase dissimilar to that in the SLS model, attaining a plateau (Glińska-Suchocka et al 2017 ; Pi et al 2021 ). In addition, the measured velocity during the propagation of shear waves across the liver at distinct values ranging from 40 Hz to 14 MHz indicates the monotonical increase of shear velocity with frequency (Glińska-Suchocka et al 2017 ; Pi et al 2021 ). Concluding from the dynamic testing on tissues of the canine liver, the KVFD model exhibited a good fit with the experimental data compared to other models, such as the KV model (Yeh et al 2015 ).…”
Section: Kelvin–voigt Fractional Derivative (Kvfd) Modelmentioning
confidence: 99%
“…The model has to satisfy both the ex vivo dynamic mechanical analysis (DMA) experiment at low frequency (1–41 Hz) and the in vivo shear wave elastography (SWE) experiment at high frequency (160–380 Hz) (Pellot-Barakat et al 2016 ). Table 5 summarizes the fitness profile for each of the three models to the shear wave velocity (Lin et al 2017 ; Pi et al 2021 ). The tabulated results reveal that the best model characterizing the rats’ mechanical properties at every steatosis stage is the Voigt model with a determination coefficient ( R 2 ) near 1.…”
Section: Kelvin–voigt Fractional Derivative (Kvfd) Modelmentioning
confidence: 99%
See 1 more Smart Citation